Shadow-Assisted Sidewall Emission for Achieving Submicron Linewidth Light Source by Using Normal UV Photolithography - Li, Junlong; Guo, Yanmin; Wang, Kun; Huang, Wei; Su, Hao; Li, Wenhao; Zhou, Xiongtu; Zhang, Yongai; Guo, Tailiang; Wu, Chaoxing (Nano-Micro Letters, 2025)
Micro light sources are crucial tools for studying the interactions between light and matter at the micro/nanoscale, encompassing diverse applications across multiple disciplines. Despite numerous studies on reducing the size of micro light sources and enhancing optical resolution, the efficient and simple fabrication of ultra-high-resolution micro light sources remains challenging due to its reliance on precise micro-nano processing technology and advanced processing equipment. In this study, a simple approach for the efficient fabrication of submicron light sources is proposed, namely shadow-assisted sidewall emission (SASE) technology. The SASE utilizes the widely adopted UV photolithography process, employing metal shadow modulation to precisely control the emission of light from polymer sidewalls, thereby obtaining photoluminescent light sources with submicron line widths. The SASE eliminates the need for complex and cumbersome manufacturing procedures. The effects of process parameters, including exposure dose, development time, and metal film thickness, on the linewidth of sources are investigated on detail. It is successfully demonstrated red, green, and blue submicron light sources. Finally, their potential application in the field of optical anti-counterfeiting is also demonstrated. We believe that the SASE proposed in this work provides a novel approach for the preparation and application of micro light sources. Highlights: 1 The submicron light sources are realized only by the normal UV photolithography process, enabling the realization of submicron light sources with arbitrary patterns. 2 A novel and efficient method for the fabrication of submicron light sources is proposed, termed shadow-assisted sidewall emission. 3 The submicron light source fabricated by the shadow-assisted sidewall emission exhibits strong scalability and has been proved to be applicable in optical anti-counterfeiting.